Does adding ginger extract to a preoperative carbohydrate drink improve outcomes in enhanced recovery after elective neuro-oncologic craniotomy? A randomized controlled trial - Kaewborisutsakul, Anukoon; Kitsiripant, Chanatthee; Churuangsuk, Chaitong; Puttarak, Panupong; Suntornlohanakul, Onnicha; Khanungwanitkul, Khanin; Rattanaburi, Athithan; Uppanisakorn, Supattra; Sungkaro, Kanisorn; Taweesomboonyat, Chin; Tunthanathip, Thara; Oearsakul, Thakul; et al. (Frontiers in Nutrition, 2025)
IntroductionIntegrating ginger, which is effective in preventing postoperative nausea and vomiting (PONV), into perioperative nutritional strategies for neurosurgical patients may enhance postoperative recovery. In this study, we evaluated whether adding standardized ginger extract to a preoperative carbohydrate drink improves postoperative outcomes in patients undergoing elective neuro-oncologic craniotomy with enhanced recovery after surgery (ERAS).MethodsThis prospective, double-blind, randomized controlled trial enrolled adult patients scheduled for elective neuro-oncologic craniotomy. Participants were randomly assigned to receive either a carbohydrate drink containing standardized ginger extract (ginger group) or an identical carbohydrate drink without it (control group) 2 h before anesthesia induction. All patients received co-treatment following the institutional ERAS protocol. The primary outcomes included the incidence of PONV, nausea severity, vomiting episodes, and rescue antiemetic use within 48 h. Secondary outcomes assessed patient well-being and metabolic and inflammatory responses.ResultsIn total, 48 patients were enrolled. The incidence of PONV did not significantly decrease (25% vs. 37.5%; p = 0.534), but vomiting episodes were significantly reduced (6 vs. 23 episodes; p = 0.003). Moreover, Poisson regression confirmed a lower incidence rate of vomiting in the ginger group than on the control group [incidence rate ratio (IRR): 0.32, 95% CI 0.16–0.80, p = 0.017]. No significant differences were found in metabolic markers, inflammatory responses, or well-being scores.DiscussionPreoperative administration of ginger-enriched carbohydrate drinks effectively reduced the number of vomiting episodes following elective craniotomy. Although other clinical and laboratory outcomes remained unchanged, this nutritional strategy may be beneficial for inclusion in ERAS protocols for elective craniotomy patients.Clinical trial registrationwww.ThaiClinicalTrial.org, identifier TCTR20220124002.